Tuneable access to indole, indolone, and cinnoline derivatives from a common 1,4-diketone Michael acceptor - El-Marrouki, Dalel; Touchet, Sabrina; Abdelli, Abderrahmen; M’Rabet, Hédi; Lotfi Efrit, Mohamed; Gros, Philippe C. (Beilstein Journal of Organic Chemistry, 2020)
A convergent strategy is reported for the construction of nitrogen-containing heterocycles from common substrates: 1,4-diketones and primary amines. Indeed, by just varying the substrates, the substituents, or the heating mode, it is possible to selectively synthesize indole, indolone (1,5,6,7-tetrahydroindol-4-one), or cinnoline (5,6,7,8-tetrahydrocinnoline) derivatives in moderate to excellent yields.
Keywords: cinnoline; 1,4-diketone; indole; indolone; N-heterocycle